(untitled) (American International Journal of Biology and Life Sciences, 2019)
Azoles are one of a cyclic derivatives of chemical heterocyclic chemical and organic compounds including g a five member di unsaturated ring structure composed of bi nitrogen atoms at position (3 and 4) and one sulfur atom at position (1).